2022
DOI: 10.3390/horticulturae9010023
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber Strigolactone Receptor CsDAD2 and GA3 Interact to Regulate Shoot Branching in Arabidopsis thaliana L.

Abstract: Previous studies identified that strigolactones (SLs) and gibberellins (GAs) interacted when controlling branching in plant shoots, but the underlying mechanism remains unknown. qRT-PCR analysis suggested that the SL receptor gene CsDAD2 was significantly upregulated in the leaves, stems, and nodes of cucumber after treatment with 50 mg/L of GA3. Furthermore, the CsDAD2 gene was cloned and introduced into wild-type Arabidopsis plants via Agrobacterium-mediated transformation. For the CsDAD2-OE lines, the endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…GAs have been reported to be involved in the photoperiodic induction of the flowering pathway [21,49]. GAs and SLs have been shown to cooperate in the regulation of stem development in cucumber [50]. Measurements of endogenous GA 3 showed that within a specific range of light duration, a higher GA 3 content promoted bolting and flowering.…”
Section: Discussionmentioning
confidence: 99%
“…GAs have been reported to be involved in the photoperiodic induction of the flowering pathway [21,49]. GAs and SLs have been shown to cooperate in the regulation of stem development in cucumber [50]. Measurements of endogenous GA 3 showed that within a specific range of light duration, a higher GA 3 content promoted bolting and flowering.…”
Section: Discussionmentioning
confidence: 99%